THE EFFECTIVENESS OF PROBLEM BASED LEARNING (PBL) AND PROJECT BASED LEARNING (PjBL) ASSISTED KAHOOT LEARNING MODELS ON STUDENT LEARNING OUTCOMES - Zam Inayah; Achmad Buchori; Agnita Siska Pramasdyahsari (Universitas PGRI Semarang, 2021)
The purpose of this study was to determine the effectiveness of problem based learning (PBL) and Project Based Learning (PjBL) models with the help of Kahoot media on student learning outcomes. The sampling technique used was cluster random sampling. Three classes were obtained, namely X ELIN as the experimental class 1, X RPL 2 as the experimental class 2, and X RPL 2 as the control class. Data collection techniques using observation, tests and documentation. The results showed (1) there were differences in student learning outcomes who received the Kahoot-assisted problem-based learning (PBL) learning model, Kahoot-assisted Project Based Learning (PjBL) and conventional classes; (2) the learning outcomes of students who received the problem based learning (PBL) learning model with the help of kahoot were better than the class that received the conventional learning model; (3) the learning outcomes of students who received the project-based learning (PjBL) assisted kahoot learning model were better than the class that received the conventional learning model; (4) the learning outcomes of students who get the Problem Based Learning (PBL) learning model with the help of kahoot and Project Based Learning (PjBL) with the help of kahoot achieve mastery individually and classically. Based on decision making through significant values, it turns out that > ie, 4.852 > 3.156, then is rejected. It can be concluded that there are differences in student learning outcomes. Judging from the average value of student learning outcomes in the experimental class I was 77.29, while the average learning outcome for the experimental class II was 77.39, and the average student learning outcome in the control class was 67.96, which means that the student learning outcomes in the control class the experiment was better than the control class students' learning outcomes.Keywords: Problem Based Learning (PBL), Project Based Learning (PjBL), Kahoot, and Learning Outcomes